1997
DOI: 10.1038/sj.bjp.0701231
|View full text |Cite
|
Sign up to set email alerts
|

NMDA receptor‐mediated pilocarpine‐induced seizures: characterization in freely moving rats by microdialysis

Abstract: 1 Pilocarpine administration has been used as an animal model for temporal lobe epilepsy since it produces several morphological and synaptic features in common with human complex partial seizures. Little is known about changes in extracellular neurotransmitter concentrations during the seizures provoked by pilocarpine, a non-selective muscarinic agonist. 2 Focally evoked pilocarpine-induced seizures in freely moving rats were provoked by intrahippocampal pilocarpine (10 mM for 40 min at a¯ow rate of 2 ml min … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(91 citation statements)
references
References 53 publications
5
82
0
2
Order By: Relevance
“…Using microdialysis in humans prior to neurological surgery, a clear association between potentially neurotoxic levels of glutamate and seizure progression has been demonstrated (During & Spencer, 1993;Wilson et al, 1996). Multiple studies in animals have similarly demonstrated an elevation in extracellular glutamate during SE (Liu et al, 1997;Smolders et al, 1997;Pena & Tapia, 1999;Ueda et al, 2002). This increase in glutamate has been implicated in the neuronal death observed after SE in these models, as antagonism of specific glutamate receptors during SE has shown to be neuroprotective (Meldrum, 1997;Rice & DeLorenzo, 1998;Hort et al, 1999;Ebert et al, 2002).…”
Section: Status Epilepticus: Causes Neuronal Injury and Increased Glumentioning
confidence: 94%
“…Using microdialysis in humans prior to neurological surgery, a clear association between potentially neurotoxic levels of glutamate and seizure progression has been demonstrated (During & Spencer, 1993;Wilson et al, 1996). Multiple studies in animals have similarly demonstrated an elevation in extracellular glutamate during SE (Liu et al, 1997;Smolders et al, 1997;Pena & Tapia, 1999;Ueda et al, 2002). This increase in glutamate has been implicated in the neuronal death observed after SE in these models, as antagonism of specific glutamate receptors during SE has shown to be neuroprotective (Meldrum, 1997;Rice & DeLorenzo, 1998;Hort et al, 1999;Ebert et al, 2002).…”
Section: Status Epilepticus: Causes Neuronal Injury and Increased Glumentioning
confidence: 94%
“…The actions exerted by ATP metabolites have not been completely understood, especially those of ADP and AMP. Increased ATP metabolism during SE may indicate increased glutamate release, which can contribute to cell death in this model [25].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is important to stop ongoing SE and limit neuronal death. Microdialysis studies in humans (During and Spencer, 1993;Wilson et al, 1996) and animals (Smolders et al, 1997;Ueda et al, 2002) have shown significant elevations in extracellular glutamate during SE. On the other hand, there are also many microdialysis studies that failed to show increases in extracellular glutamate during SE (Bruhn et al, 1992;Millan et al, 1993).…”
Section: Discussionmentioning
confidence: 99%